Perception of medical students about the extension activity "super powerful vaccines": Experience report - Moreira , Mayara dos Santos Camelo; Chianca , Ananza Ávila Castelo Branco; Carvalho, Erica Giovanna Mailho Ismael de; Monteiro , Alana Dionizio Carneiro; Machado , Karine Oliveira Alves; Branco, Bruna Castelo; Araujo , Cecília Fernanda Batista de; Pinto, Nathália Oliveira; Neto, José Fragoso da Silva; Bezerra, Andressa Fernandes; Filho , Jurandir Abrantes de Oliveira; Antonino , Lilian Salustiana da Silva; et al. (Seven Editora, 2023)
Vaccination should be understood as the most effective measure to prevent diseases, contributing directly to the decrease in morbidity and mortality caused by infectious pathologies preventable by vaccination, including in children. Brazil has been a world reference in vaccination for years, but in the last ten years there has been a sharp drop in the number of users benefiting from immunizations, demonstrating a greater vulnerability, specifically to children. The present work is an experience report that seeks to describe the experiences of medical students of the AFYA School of Medical Sciences. The extension action was entitled "Super Powerful Vaccines", held at the Family Health Unit (USF) São Rafael, João Pessoa-PB. Playful, dynamic and human approaches were carried out to welcome users, in order to expand vaccination coverage in the community. The extension action allowed an increase in the number of vaccines applied, revealing positive results in view of the strategies used. The experience provided an enriching moment for the students, expanding the sense of citizenship and represented a tool for achieving humanized medical training, providing a reflection on the importance of teamwork in this scenario and raising awareness about the health needs of the population. DOI:https://doi.org/10.56238/globalhealthprespesc-017